Sources of sport confidence, imagery type and performance among competitive athletes: the mediating role of sports confidence - Levy, A. R.; Perry, J.; Nicholls, A. R.; Larkin, D.; Davies, J. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: This study explored the mediating role of sport confidence upon (1) sources of sport confidence-performance relationship and (2) imagery-performance relationship.